2003
DOI: 10.5453/jhps.38.332
|View full text |Cite
|
Sign up to set email alerts
|

Vodnyi: a Long-term, Low-level Radiation Exposure Field Site in Russia

Abstract: The Vodnyi site in the Komi Republic of Russia represents a unique radioecological field site. The history of industrial operations associated with radioactivity here spans the period 1931 to 1956. Initial operations focused on the extraction of radium from groundwater [226Ra concentration up to 7, 840 pCi/L (290 Bq/L) ], In 1947, the extraction of uranium and radium from ores began. Radionuclide contamination in the Vodnyi region includes soils that had been in long-term contact with radium-rich groundwater, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…However, studies of tufted vetch (Vicia cracca), a forage plant growing on UMT and Ra production wastes at the Otvally site in Vodnyi, in the Komi Republic of Russia (Taskaev et al, 2003) showed that internally deposited 226 Ra contributes a major fraction of the dose. That dose can be above the threshold for biological effects; observed effects that correlated directly with the calculated absorbed dose for seeds at the site include the frequency of chromosome aberrations in the meristematic root-tip cells of seedlings, the germination rates of seeds, and the survival rates of sprouts of seeds (Evseeva et al, 2009).…”
mentioning
confidence: 99%
“…However, studies of tufted vetch (Vicia cracca), a forage plant growing on UMT and Ra production wastes at the Otvally site in Vodnyi, in the Komi Republic of Russia (Taskaev et al, 2003) showed that internally deposited 226 Ra contributes a major fraction of the dose. That dose can be above the threshold for biological effects; observed effects that correlated directly with the calculated absorbed dose for seeds at the site include the frequency of chromosome aberrations in the meristematic root-tip cells of seedlings, the germination rates of seeds, and the survival rates of sprouts of seeds (Evseeva et al, 2009).…”
mentioning
confidence: 99%
“…Thick walled wooden pipes were used to convey groundwater from wells to the plant (Evseeva et al, 2000;Taskaev et al, 2003). Leakage and piping failures were common, resulting in very irregularly distributed soil contamination.…”
Section: Vodnyi Settlementmentioning
confidence: 99%
“…At a site in the Komi Republic of northwestern Russia (Taskaev et al, 2003), soils are contaminated with radium-rich brines and have 226 Ra concentrations of about 26 Bq g À1 (700 pCi g À1 ) and dose rates to soil invertebrates of about 10 mGy day À1 (1 rad day À1 ). Krivolutzky (1987) has shown decreases in population size and reproduction rates, and histological changes in mid-gut epithelium in earthworms at this site compared to uncontaminated control sites.…”
Section: Radiation Effects Studiesmentioning
confidence: 99%
“…(f) The past decade has seen a major increase in reports on radioecological impacts of U milling activities on microorganisms, plants, invertebrates, and higher animals. The easing of political barriers is creating the opportunity to access the wealth of radioecological studies done on the fate and impact of radionuclides associated with U ore processing in the FSU (Taskaev et al, 2003).…”
Section: Introductionmentioning
confidence: 99%